Pengujian Reliabilitas Malang Kabupaten Tourism Intelligence Center (MATIC) Menggunakan Pengujian Eksplorasi Metafora Tur Pariwisata - Arga Bagus Santosa; Titis Sari Putri; Muhammad Tosan Bingamawa (POLITEKNIK NEGERI JAKARTA, 2025)
The tourism sector is an industry that is able to contribute to improving the economy and public welfare, and has even defeated the oil and coal sectors which have been the leading sectors. Digital services in the tourism sector have been developed by several regional governments, both in the form of mobile applications and websites for the promotion and marketing of tourist destinations, as well as various tourism information services, such as infrastructure, accommodation, cultural activities, locations, and so on. Malang Regency Tourism Intelligence Center (MATIC) is one of the digital public services in the tourism sector developed by the Malang Regency Government. MATIC is a big data and intelligence-based tourism service application that manages and analyzes tourism data comprehensively, which is developed into a one-stop application for tourism and creative economy information. Public service software is an Electronic-Based Command System (SPBE) which has the function of disseminating and providing public services, so it should have good and reliable performance in order to provide the best service to the public as application users. This study aims to support the implementation of MATIC by ensuring the reliability or provision of applications through software testing with tourism tour metaphor exploration testing techniques. The study presents exploration testing steps starting from the test preparation stage, test implementation, and test results that show the findings of 22 deficiencies or defects. The level of defects found were 14 low errors, 5 medium errors, and 3 high errors. Defects were found from three variations of tourism tour metaphor testing techniques, namely money tours, supporting actor tours, and supermodel tours.